How does the domiciliation decision affect mutual fund fees? - Gunnar Lang; Matthias Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In this paper, we analyze whether the domiciliation decision of mutual funds has an impact on fund fees. To explain the fee price-setting of mutual funds, we consider characteristics specific to funds, fund companies, and countries. We find that fees vary considerably across fund types and countries. Positive impacts of financial market integration can be confirmed, though funds set up under the UCITS directive are more expensive. If funds are sold in multiple countries it drives up fees; however, these higher costs for the investor are outweighed by economies of scale that can be generated if the domiciliation is in a specialized financial center, such as Luxembourg. Larger funds and funds that are set up by specialized or larger fund companies have significantly lower fees.
Keywords: F36; G15; G18; G20; L11; 330; Mutual Funds; Financial Regulation; Market Integration